BCD cards: A tool for designing theory-based behavior change technologies - Konstanti, Chrysanthi; Karapanos, Evangelos; Markopoulos, Panos (My University, 2019)
There is a wealth of theoretical knowledge around behavior change theories and strategies. However, due to the lack of accessibility of that knowledge to designers, designing theory-based behavior change technological interventions can be challenging. Card-based design tools can make academic knowledge accessible to designers, providing a structured and creative design process. In this study, we present the Behavior Change Design Cards (BCD Cards) - a card deck developed from two behavior change theoretical models, the Transtheoretical Model of Behavior Change and a Taxonomy of 93 Behavior Change Techniques. Through an empirical study, we aim at evaluating the impact of the tool on designers’ creativity, their capacity to create theoretically-grounded designs, as well as the perceived usefulness and ease of use of the BCD cards as a supporting tool in the design of behavior change technologies.
Keywords: Behavior Change; Behavior Change Technologies; Design Cards; Design Tools